Property lease: Law 27.551 and its connection with the emergency legislation - Federico Manuel Lértora (Revista de la Facultad de Ciencias Económicas, 2020)
Since July 1st., 2020, Law 27.551 entered into effectiveness in our country, changing the Civil and Commercial Code mainly regarding the property lease contract and in particular regarding the property with residence purposes lease. The legislation is divided into four headings, each of them corresponding to the modifications of the Code, the passing of complementary normative, the creation of the National Program of social ‘rent’, and the promotion of alternative means of conflict resolutions, respectively, reaffirming a protective nature in sights of the protection of the lessee. This paper will focus on the first two headings, gathering different jurists’ opinions in that regard. Additionally, it will analyze the connection between Law 27.551 and the emergency legislation passed as a result of de Covid-19 pandemic regarding leases, on the grounds of the so called “sources dialogue”.